Agama dan Benturan Peradaban - Syarifuddin Syarifuddin (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2014)
The presence of religion, especially the religions of mission, in human life has established a separate civilization characteristics which can lead to a clash of civilization which is assumed in the form of inter-group conflict of civilizations. The clash believed to be a necessity is mainly triggered by modernity which in the end led to the secularization. The above assumptions initiated by Huntington still can be criticized for several reasons. However, the tolerance between civilizations should be implemented. In this regard, multiculturalism as the willingness to accept other groups equally as an entity regardless of cultural differences, ethnicity, gender, language, religion or country becomes important to be discussed. Likewise, vertical and horizontal dialogue should be the most essential way to cultivate harmonious life among all religious people.